Pengaruh Akreditasi Terhadap Peningkatan Mutu Pelayanan Rumah Sakit - Solehudin Solehudin; Sancka Stella Ganiasnda Sihura (Jurnal Medika Husada, 2023)
Hospital accreditation is one way to assess the quality of hospital services. Improving the quality of hospital services is very important, as hospitals provide the most critical and dangerous services in the healthcare system, and their target activity is human life. The aim of this research was to determine the influence of accreditation on the improvement of service quality after the Covid-19 pandemic. The research used a quantitative method with a cross-sectional approach. The data used in this research were secondary data. The research was conducted at Depok Private Hospital from January to March 2022. The data analysis used the General Linear Model Repeated Measure statistical test. The results of the study showed that the value of hospital service quality based on the Greenhouse-Geisser sig 0.035 < 0.05. Thus, it can be said that accreditation affects the quality of hospital services with a trend of increasing service quality values from January to December 2022. The conclusion of the study is that the quality of service in hospitals after the Covid-19 pandemic has changed. There are differences in service quality values every month. Service quality tends to improve during the year 2022.